The Acquisition of Adjective Gradation in Lithuanian Children with Developmental Language Disorder at Preschool and Pre-primary School Age - Kamandulytė-Merfeldienė, Laura (Taikomoji kalbotyra, 2021)
The aim of the study is to examine Lithuanian children’s with developmental language disorder abilities in forming comparative and superlative degrees of adjectives. We report the data from a Sentence Completion Study with 80 Lithuanian children with developmental language disorder (age range 4;6-6;5) and 80 typically developing Lithuanian children (age range 4;6-6;5). For the picture-based comparative and superlative formation task, 30 adjectives were selected to control for the following variables in Lithuanian: obligatory morphonological palatalisation of root-final dentals, the variables syllabic length (bisyllables vs. trisyllables) and underived vs. derived adjectives.The results confirmed our first hypothesis that correct production of both comparatives and superlatives is influenced by several factors: the general length effect, morphological complexity of the adjective (whether derived or not), morphotactic transparency/opacity (opacifying morphonological palatalization). The results confirmed our second hypothesis that Lithuanian children with developmental language disorder faced more difficulties in performing the adjective gradation task than typically developing children. In addition, the results have shown that children’s performance on comparatives was better than on superlatives. The better performance of comparatives could be explained by the fact that the superlative is morphosemantically and morphotactically more marked than the comparative. On the other hand, it could be, according to Layton and Stick’s hypothesis (1979), that the later acquisition of the superlative suffix is due to limitations in cognitive and perceptual abilities, which may be seen as one cause of morphosemantic markedness.
Keywords: adjective; gradation; comparative; superlative; language impairment; developmental language disorder